2022
DOI: 10.1111/ijlh.13846
|View full text |Cite
|
Sign up to set email alerts
|

Differences between capillary and venous blood counts in children—A data mining approach

Abstract: Background Capillary sampling of blood counts is a well‐established alternative to venipuncture in paediatrics. However, the sampling method has to be considered when interpreting test results, as measurements differ. Ethical and practical considerations prevent simultaneous venous and capillary sample acquisition in comprehensive paediatric cohorts that span all ages for the purpose of a direct method comparison, resulting in uncertainty regarding the interpretation of capillary test results. Methods We appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Bias analysis indicated acceptable variation between capillary and venous measurements for the majority of CBC parameters when desirable TEa was selected as a decision threshold. Our results on comparability between venous and capillary measurements are in line with results of previous studies 8,11,13,15,18 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bias analysis indicated acceptable variation between capillary and venous measurements for the majority of CBC parameters when desirable TEa was selected as a decision threshold. Our results on comparability between venous and capillary measurements are in line with results of previous studies 8,11,13,15,18 …”
Section: Discussionsupporting
confidence: 92%
“…Our results on comparability between venous and capillary measurements are in line with results of previous studies. 8,11,13,15,18 To determine whether CBC parameters are potentially suitable for remote sampling and delayed analysis, we aimed to extend previous research and assess long-term CBC stability. Red cell indices, such as erythrocyte counts, hematocrit, hemoglobin, MCH, MCV, MPV, RDW, and platelet counts were generally most stable (up to 168 h) when stored at 4 C, in agreement with previous studies on stability up to 72 h. 10,16,19 Hematocrit, MCV, and RDW measurements gradually increased over time at room temperature (21-22 C) and 30 C.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The detection results showed that the difference between the hemoglobin content of the two was 6.5g/L, the difference between the hematocrit was 2.38%, and the difference between the distribution width of red blood cells was 0.4%. Therefore, capillary blood sampling can replace venous blood sampling, with certain feasibility [8]. Zhang et al screened structural materials in peroxide solar cells using data mining techniques and stored their structural information in a structural database.…”
Section: Related Workmentioning
confidence: 99%
“…After obtaining the initial position of the target user, KNN precise positioning is performed using the MR fingerprint algorithm, and the precise positioning of the target user is obtained using the cosine distance algorithm. The expression formula is as follows (8).…”
Section: Xymentioning
confidence: 99%